(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
In the modern world, a child is raised in a technologically enhanced setting. This significantly modifies kids’ perceptions and learning styles, proves the value of using interactive digital tools with young kids, and motivates them to adopt appropriate speech and behavior. Speech restraint exercises are essential. This study will focus on the use of pedagogical technology tools used in preschool institutions to encourage discussion about the future uses of digital technologies, examine theoretical literature, and correct speech therapy.